‘NO ONE KNOWS ANYTHING’: KINSHIP CAREGIVERS AND THEIR EXPERIENCES WITH SOCIAL SERVICES IN POLAND - GRZELKA, MICHALINA; SZOSTAKOWSKA, KATARZYNA (Society Register, 2019)
This paper provides a window into the ways kinship caregivers of elderly persons and people with disabilities describe their experiences with social services in Poland. Kinship caregivers in Poland, the majority of whom are women, often struggle with inadequate access to social services dedicated to people with disabilities and the elderly. One of the major issues faced by caregivers who try to secure these services, are complex rules and regulations which frequently make it very difficult to access information and assistance. By the way of critical discourse analysis, this paper examines letters by and interviews with kinship caregivers in Poland. These two data sets present the problems faced by kinship caregivers of elderly persons and people with disabilities who are frequently left frustrated by their interactions the social services system and its gatekeepers. Therefore, the authors hope that this study will provide policymakers responsible for social policy in Poland with some useful insights and suggestions.